Spiritual Formation in an Australian Baptist Theological College: A Survey-based Case Study1. Issue 2 (November 2015) - Hussey, Ian
Abstract : This article reports on preliminary research into spiritual formation at a Baptist theological college in Queensland, Australia. In response to a growing awareness of the need to quantify spiritual formation (as defined by Queensland Baptists) a 55 item inventory was developed and made available to all 250 college students with a response rate of nearly 50 per cent (122 students). The survey enabled the comparison of students in different demographic segments and at different stages in their theological education. The research suggests that in the areas where the College has been intentionally allocating resources and emphasis (as driven by its aspirational Graduate Attributes Statement) it has largely been effective in spiritual formation. However the research also suggests that development in some areas has resulted in retardation in other areas.